(untitled) (Research, Society and Development, 2022)
This study aimed to evaluate the properties of soda lignin obtained from an unconventional and abundant waste - the rambutan peel - since lignin has been shown as the most promising natural organic feedstock alternative to petroleum for polymer science. FTIR analysis and pH measurements have confirmed the acidic form of lignin, which has shown solubility in a wide range of polarities and so many solvents, making its insertion easy on polymeric matrices. While the ability to absorb UV-light was higher than commercial lignin tested as reference, the morphology and size distribution at microscopic level were less regular than that. When added to a starch-based film, the lignin decreases its natural affinity for water, improving the barrier properties, as well as increasing its thermal resistance. Microorganisms could be developed easily on starch-based films containing this kind of lignin. This material, still underreported for technological applications, points towards as promisor to be a component or additive in polymeric matrices.